PRMT5 Inhibition Promotes PD-L1 Expression and Immuno-Resistance in Lung Cancer - Hu, Rui; Zhou, Bingqian; Chen, Zheyi; Chen, Shiyu; Chen, Ningdai; Shen, Lisong; Xiao, Haibo; Zheng, Yingxia (Frontiers in Immunology, 2022)
Protein arginine transferase 5 (PRMT5) has been implicated as a key modulator of tumorigenesis, and promotes tumor cells proliferation, invasion and metastasis. Researchers have largely focused on PRMT5 control of tumor intrinsic changes; however, PRMT5 effects on the tumor microenvironment and on immune cells were largely unknown. Here, we found that targeting PRMT5 by genetic or pharmacological inhibitor reduced tumor progression in the immunocompromised mice; however, the treatment effect was weekend in immunocompetent mice. We revealed that PRMT5 inhibition not only inhibited tumor cell survival, but also induced tumor cells expressing genes enriched in type1 INF response and CD274 in vitro and in vivo, which activated PD1/PDL1 axis and eliminated T cells anti-tumor ability. Mechanically, PRMT5 regulated CD274 gene expression through symmetric dimethylation of histone H4R3, high level of H3R4me2s deposition on the STAT1 and CD274 promoter loci, thus inhibition of PRMT5 induced STAT1 and CD274 expression in lung cancer treatment. PRMT5 inhibitors represented a double-edged sword as they might selectively kill cancer cells, but might also critically influence the antitumor immune response. Combination of PRMT5 inhibition and ani-PD-L1 therapy led to increase the number and enhance the function of tumor infiltrating T cells. Our findings addressed an unmet clinical need that applying combination of PRMT5 inhibition and anti–PD-L1 therapy could be the promising strategies for lung cancer therapy.